Francisella tularensis-specific antibody levels in sera from Swedish patients with suspected tularemia during a 13-year period - Lindgren, Helena; Liu, Xijia; Sjöstedt, Anders (Frontiers in Cellular and Infection Microbiology, 2024)
For a majority of tularemia patients, serology is the basis for the diagnosis. We performed a retrospective analysis of the presence of Francisella tularensis-specific antibodies in serological samples from patients with suspected tularemia analyzed during the period 2010 -2022 at the University Hospital of Umeå in Sweden, a national reference laboratory. In total, some 15,100 serum samples had been analyzed for the presence of IgG and IgM antibodies by ELISA during the 13-year period. Overall, there were higher number of samples with IgG positive or borderline titers, 2,522 and 921, respectively, than with IgM positive or borderline titers, 1,802 and 409, respectively.Repeated samples were obtained from some 1,930 individuals and approximately a third of the cases, which were initially seronegative, had seroconverted when resampled. Peak number of samples were recorded in August and September, > 3,000. Annual numbers varied greatly and peak numbers were observed in 2015 and 2019, 1,832 and 2,250, respectively, whereas some other years the numbers were 700 -800. There was also much variation in the annual and monthly percentages of positive samples and they varied between less than 10% to greater than 20%. The highest percentages of positive samples were recorded in September and October. IgG and IgM titers declined with age and these differences were highly significant for IgG titers, with decreasing average titers for each 20-year interval. Collectively, the data demonstrate the marked annual and seasonal variations in tularemia sampling occurring in Sweden. Also, the proportion of positive samples increased during months and years with peak number of samples. Another notable finding was that average antibody titers decreased with increased age.